Binder containing copolymer composition, negative electrode for secondary battery containing said binder, and secondary battery containing said negative electrode
By using a polymer material formed by copolymerization of acetaldehyde and amino alcohol as the adhesive for the negative electrode of lithium-ion battery, the problems of reduced conductivity and cyclic stability caused by volume changes during charging and discharge of silicon-based materials are solved, and a higher binding force and capacity retention rate is achieved.
Patent Information
- Application Number
- JP2024553714
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-15
- Filing Date
- 2023-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-03-13
AI Technical Summary
In the existing lithium-ion secondary batteries, the volume of the silicon-based negative electrode material changes greatly during the charging and discharging process, resulting in a decrease in conductivity and separation of the electrode layer from the electrolyte, which in turn affects the cycle stability and capacity retention rate of the battery.
The polymer material formed by copolymerization of acetaldehyde-based units and amino alcohol units is used as the adhesive for the negative electrode. The bonding force of the adhesive is enhanced through strong hydrogen bonding and coordination bonds with the silicon-based anode material and the electrode collector, and the flexibility is provided through the vinyl skeleton structure to cope with volume changes.
The binding force and stability of the negative electrode are significantly improved, the volume changes of the silicon-based material are suppressed, the cycle life of the battery is extended, and the capacity retention rate is improved.
Smart Images

Figure 2025509389000001 
Figure 2025509389000002 
Figure 2025509389000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a copolymer composition that can be used as a binder, and a slurry, an electrode, and a secondary battery each containing the same. [Background technology]
[0002] Lithium secondary batteries have a high energy density and are widely used in the electrical, electronic, communication and computer industrial fields. In addition to small lithium secondary batteries for portable electronic devices, their application fields are expanding to high-capacity secondary batteries for hybrid vehicles, electric vehicles and the like.
[0003] As the range of applications expands, lithium secondary batteries are required to have high capacity as well as long life characteristics. One method for increasing the capacity of lithium secondary batteries is to use an active material containing silicon atoms in the negative electrode.
[0004] When using active materials containing silicon atoms, which have a larger amount of lithium inserted / deintercalated compared to conventional carbon-based active materials, it is expected that the battery capacity will improve. However, silicon-containing active materials have a large volume change associated with the insertion / deintercalation of lithium, so the negative electrode active material layer expands and contracts significantly during charging and discharging.
[0005] As a result, the conductivity between the negative electrode active materials decreases, or the conductive path between the negative electrode active material and the current collector is interrupted, causing problems such as a deterioration in the cycle characteristics of the secondary battery.
[0006] However, the various binders that have been developed so far (PAA, PAA / CMC, Na-PAA, crosslinked PAA, alginate, PVA, etc.) have insufficient adhesive strength or make the electrodes excessively brittle and lack durability, so it is difficult to expect them to solve the volume expansion problem mentioned above.
[0007] Therefore, there is a demand for a binder that can solve these problems and ensure the capacity maintenance rate of secondary batteries. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Republic of Korea Patent Publication No. 10-2016-0024921 Summary of the Invention [Problem to be solved by the invention]
[0009] Therefore, an object of the present invention is to provide a copolymer composition having excellent water solubility and dispersibility, which can enhance the dispersion stability of a slurry composition.
[0010] Another object of the present invention is to provide a slurry composition using the copolymer composition, which has excellent binding strength and electrode expansion suppressing ability.
[0011] In addition, the present invention provides an electrode (particularly, a negative electrode) having excellent performance to which the slurry composition is applied, and a secondary battery including the electrode and having excellent capacity retention rate per cycle.
[0012] However, the problems to be solved by the present application are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]
[0013] One aspect of the present application is a method for producing a polymerizable composition comprising: a first copolymer including a vinyl alcohol monomer unit and a vinyl amine monomer unit; and a second copolymer including a vinyl alcohol monomer unit and an acrylic acid salt-based monomer unit. A copolymer composition is provided.
[0014] Another aspect of the present application is a copolymer composition comprising: A negative electrode active material, An anode slurry is provided.
[0015] Yet another aspect of the present application is a battery comprising: a current collector; a negative electrode active material layer including the copolymer composition formed on the current collector, A negative electrode is provided.
[0016] Yet another aspect of the present application is a method for producing a method for manufacturing a semiconductor device comprising the steps of: The negative electrode is included. A secondary battery is provided. Effect of the Invention
[0017] The copolymer composition of the present invention has excellent flexibility, water solubility and dispersibility, and improves the dispersion stability of the negative electrode slurry composition. It also enhances the binding strength with the negative electrode current collector, suppresses the expansion of the negative electrode, and improves the capacity retention rate per cycle of the secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention, however, these examples are merely examples of the present invention and do not define the scope of the invention.
[0019] Prior to this, the terms and words used in this specification and claims should not be interpreted limited to their ordinary or dictionary meanings, but should be interpreted with meanings and concepts that correspond to the technical ideas of the present invention, in accordance with the principle that an inventor can appropriately define the concepts of terms in order to explain his / her invention in the best possible way.
[0020] Therefore, it should be understood that the configuration of the embodiment described in this specification is merely one of the most preferred embodiments of the present invention and does not fully represent the technical ideas of the present invention, and that there may be various equivalents and modifications that can replace them at the time of this application.
[0021] In this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise. It should be understood that in this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, and do not preclude the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.
[0022] In this specification, the terms "from" and "to" in the expressions "from a to b" and "a~b" that indicate numerical ranges are defined as ≧a and ≦b.
[0023] The copolymer composition according to one embodiment of the present application may include a first copolymer including a vinyl alcohol monomer unit and a vinyl amine-based monomer unit, and a second copolymer including a vinyl alcohol monomer unit and an acrylic acid salt-based monomer unit.
[0024] In one embodiment, the first copolymer may additionally include at least one selected from a vinyl acetate monomer unit and an N-vinylformamide monomer unit, and the second copolymer may additionally include at least one selected from an acrylate monomer unit and a vinyl acetate monomer unit.
[0025] The first copolymer contains a hydroxyl group and an amine group, and therefore when used as a binder for a negative electrode slurry, it can form strong hydrogen bonds with silicon, which is a negative electrode active material, and form coordinate bonds with the negative electrode current collector, thereby increasing the binding strength between the silicon and the current collector.
[0026] Meanwhile, the second copolymer can impart flexibility to the binder of the negative electrode slurry based on the ethylene skeleton structure, and can suppress the volume change of silicon, which is the negative electrode active material. In addition, the alkali metal ions substituted at the ends of the acrylic acid salt-based monomer units can contribute to improving ion conductivity. In addition, the stretched chains can interact with the negative electrode active material to form a dense porous electrode, and a stable SEI layer can be formed.
[0027] The hydroxyl groups of the first copolymer and the carboxyl groups of the second copolymer can be chemically and / or physically crosslinked, which can suppress the volume change of silicon, which is the negative electrode active material.
[0028] In an embodiment, the vinyl amine-based monomer unit of the first copolymer may be, but is not limited to, at least one selected from the group consisting of vinyl amine and 1-methylvinyl amine.
[0029] In addition, the acrylic acid salt-based monomer unit of the second copolymer may be at least one selected from the group consisting of acrylic acid and methacrylic acid, but is not limited thereto.
[0030] In an embodiment, the N-vinylformamide-based monomer unit of the first copolymer may be, but is not limited to, one or more selected from the group consisting of N-vinylformamide and N-isopropenylformamide.
[0031] In addition, the acrylate-based monomer unit of the second copolymer may be at least one selected from the group consisting of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, sec-butyl acrylate, sec-butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, and ethylhexyl methacrylate, but is not limited thereto.
[0032] In one embodiment, the first copolymer may contain 50 mol % to 90 mol % of the vinyl alcohol monomer unit and 1 mol % to 50 mol % of the vinylamine monomer unit, based on a total content of 100 mol % of the first copolymer.
[0033] In one embodiment, the second copolymer may contain 1 mol % to 30 mol % of the vinyl alcohol monomer unit and 50 mol % to 90 mol % of the acrylic acid salt-based monomer unit, based on a total content of 100 mol %.
[0034] The content of the first copolymer and the second copolymer can be adjusted by changing the degree of hydrolysis during the preparation of the first copolymer and the second copolymer.
[0035] In one embodiment, the first copolymer may be represented by the following Formula 1, and the second copolymer may be represented by the following Formula 2:
[0036] [ka]
[0037] In the above Chemical Formula 1, 0≦x≦15 mol%, 50≦y≦90 mol%, 0≦m≦30 mol%, and 1≦n≦50 mol%. In the above formula 1, x, y, m and n represent the mol% of each monomer unit.
[0038] [ka]
[0039] In the above Chemical Formula 2, R1 and R2 are different or identical to each other, and each independently represents hydrogen or a linear or branched hydrocarbon having 1 to 5 carbon atoms; R3 is a hydroxyl (-OH) group; M is an alkali metal; 0≦a≦5 mol%, 50≦b≦90 mol%, 0≦c≦5 mol%, and 1≦d≦30 mol%. In the above Chemical Formula 2, a, b, c, and d represent the mol% of each monomer unit.
[0040] Furthermore, M in the above Chemical Formula 2 may be any one selected from the group consisting of lithium (Li), potassium (K) and sodium (Na), but is not limited thereto.
[0041] Meanwhile, R1 and R2 in Chemical Formula 2 may each independently be any one selected from the group consisting of hydrogen, methyl, ethyl, n-propyl, iso-propyl, n-butyl, iso-butyl, sec-butyl, tert-butyl, and n-pentyl, but are not limited thereto.
[0042] In one embodiment, the copolymer composition may comprise 10% by weight or more and 90% by weight or less of the first copolymer and 10% by weight or more and 90% by weight or less of the second copolymer, based on a total weight of 100% by weight of the copolymer composition.
[0043] Within the range of the first copolymer and the second copolymer in the copolymer composition, the higher the content ratio of the first copolymer, the more the binding strength of the negative electrode can be improved when the copolymer composition is used as a negative electrode binder.
[0044] In addition, as the content ratio of the second copolymer within the content range of the first copolymer and the second copolymer in the copolymer composition becomes higher, when the copolymer composition is used as a negative electrode binder, the dispersibility and stability of the negative electrode slurry can be further improved.
[0045] When the copolymer composition is used as a negative electrode binder in such an amount that the contents of the first copolymer and the second copolymer in the copolymer composition exceed the range of the present application, one or more of the dispersion stability of the negative electrode slurry composition, the binding strength of the negative electrode, and the characteristics of the secondary battery may be deteriorated.
[0046] In particular, electrodes with low adhesion to the current collector may experience detachment during the drying and rolling processes, and when the rolling density of the electrode is increased, separation of the applied slurry from the electrode may occur. In addition, when the battery is operated, low adhesion to the electrode plate may cause the electrode to swell in the electrolyte and detach, resulting in a decrease in the operating stability of the battery.
[0047] In one embodiment, the first copolymer may be a random or block copolymer and the second copolymer may be a random or block copolymer.
[0048] In one embodiment, the number average molecular weight of the first copolymer may be 10,000 or more and 1,000,000 or less, and the number average molecular weight of the second copolymer may be 10,000 or more and 1,000,000 or less.
[0049] Meanwhile, the first copolymer can be prepared by hydrolysis of a copolymer containing vinyl acetate monomer units and N-vinylformamide-based monomer units.
[0050] That is, the vinyl acetate monomer unit and the N-vinylformamide monomer unit of the first copolymer can be hydrolyzed to vinyl alcohol monomer unit and vinyl amine monomer unit, respectively.
[0051] Also, the second copolymer can be prepared by hydrolysis of a copolymer containing an acrylate-based monomer unit and a vinyl acetate monomer unit.
[0052] That is, the acrylate-based monomer unit and the vinyl acetate monomer unit of the second copolymer can be hydrolyzed into an acrylic acid salt-based monomer unit and a vinyl alcohol monomer unit, respectively.
[0053] The hydrolysis for producing the first copolymer and the second copolymer can be carried out using, but is not limited to, an alkali metal hydroxide.
[0054] According to yet another aspect of the present disclosure, a negative electrode slurry may include the copolymer composition and a negative electrode active material.
[0055] That is, the copolymer composition can be used as a binder for a negative electrode.
[0056] The peel strength between the negative electrode active material layer formed using the negative electrode slurry and the copper current collector is 4 dyne / cm 2 It may be 11 dyne / cm or more. 2 It may be the following.
[0057] The negative electrode active material may be a compound containing one or more selected from the group consisting of carbon-based materials, silicon, alkali metals, alkaline earth metals, group 13 elements, group 14 elements, transition metals, and rare earth elements, and preferably may be silicon or a compound containing silicon.
[0058] Examples of the carbon-based material include, but are not limited to, artificial graphite, natural graphite, hard carbon, soft carbon, etc. The negative electrode active material containing silicon is not particularly limited as long as it is silicon or a compound containing silicon, and preferably is Si, SiO x (0 < x < 2), Si-Y alloy (wherein Y is an alkali metal, alkaline earth metal, group 13 element, group 14 element, transition metal, rare earth element, or a combination thereof, and is not Si), and one or more selected from the group consisting of Si-C composites.
[0059] When the negative electrode active material containing silicon and another negative electrode active material are mixed and used, the negative electrode active material containing silicon may be contained in an amount of 8% by weight or more based on the total weight of the negative electrode active material.
[0060] The negative electrode active material may be contained in an amount of 50 to 90% by weight, preferably 60 to 80% by weight, based on the total weight of the negative electrode active material layer.
[0061] When the negative electrode active material is contained in an amount of less than 50% by weight, the energy density decreases and a high-energy density battery cannot be manufactured. When the negative electrode active material is contained in an amount of more than 90% by weight, the contents of the conductive material and the binder decrease, the electrical conductivity decreases, and the adhesive force between the electrode active material layer and the current collector may decrease.
[0062] Meanwhile, the copolymer composition binder of the present application may be included in an amount of 1 to 35 wt % based on the total weight of the negative electrode slurry. If the copolymer is included in an amount of less than 1 wt %, the physical properties of the negative electrode may be deteriorated, and the negative electrode active material and the conductive material may fall off, whereas if the copolymer is included in an amount of more than 35 wt %, the ratio of the negative electrode active material and the conductive material may be relatively reduced, and the battery capacity may be reduced, and the electrical conductivity of the negative electrode may be reduced.
[0063] In addition, the negative electrode slurry may further include a polymer in addition to the copolymer composition of the present application. Specific examples of the polymer include, but are not limited to, polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylic acid (PAA), metal polyacrylate (Metal-PAA), polymethacrylic acid (PMA), polymethyl methacrylate (PMMA), polyacrylamide (PAM), polymethacrylamide, polyacrylonitrile (PAN), polymethacrylonitrile, polyimide (PI), chitosan, starch, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, hydroxypropyl cellulose, regenerated cellulose, and various copolymers thereof.
[0064] A negative electrode according to yet another aspect of the present application may include a current collector and a negative electrode active material layer including the copolymer composition of the present application formed on the current collector.
[0065] The negative electrode active material layer may further include a conductive material. The conductive material is used to further improve the conductivity of the negative electrode active material. The conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery. For example, graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fiber such as carbon fiber or metal fiber; metal powder such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxide such as titanium oxide; polyphenylene derivatives, etc. may be used.
[0066] The conductive material may be contained in an amount of 5 to 30 wt %, preferably 15 to 25 wt %, based on the total weight of the negative electrode active material layer. If the conductive material is contained in an amount less than 5 wt %, the electrical conductivity of the negative electrode is reduced. If the conductive material is contained in an amount exceeding 30 wt %, the ratio of the silicon-based negative electrode active material to the binder is relatively reduced, resulting in a reduced battery capacity, and since the binder content must be increased to maintain the negative electrode active material layer, the negative electrode active material content is reduced, making it impossible to manufacture a battery with a high energy density.
[0067] In the negative electrode of the present application, since the negative electrode active material layer contains the copolymer composition of the present application, volume expansion of the negative electrode active material that occurs during charging and discharging of the secondary battery can be suppressed, and the capacity retention rate per cycle can be improved.
[0068] The negative electrode can be manufactured by (a) producing a negative electrode active material layer-forming composition containing a negative electrode active material and the copolymer composition of the present application, and (b) applying the negative electrode active material layer-forming composition onto a negative electrode current collector and then drying it.
[0069] The composition for forming the negative electrode active material layer is prepared in the form of a negative electrode slurry. The solvent for preparing the slurry should be easy to dry, and most preferably should be capable of dissolving the copolymer composition binder of the present application well and maintaining the negative electrode active material in a dispersed state without dissolving it.
[0070] The solvent according to the present application may be water or an organic solvent, and the organic solvent may be one or more selected from the group consisting of methylpyrrolidone, dimethylformamide, isopropyl alcohol, acetonitrile, methanol, ethanol, and tetrahydrofuran.
[0071] The negative electrode active material layer forming composition can be mixed by a conventional mixer such as a latex mixer, a high-speed shear mixer, or a homogenizer in a conventional manner.
[0072] The step (b) is a step of applying the composition for forming a negative electrode active material layer prepared in the step (a) onto a negative electrode current collector and then drying the composition to prepare a negative electrode for a lithium secondary battery.
[0073] Specifically, the negative electrode current collector may be selected from the group consisting of copper, stainless steel, titanium, silver, palladium, nickel, alloys thereof, and combinations thereof. The stainless steel may be surface-treated with carbon, nickel, titanium, or silver, and the alloy may be an aluminum-cadmium alloy. In addition, baked carbon, a non-conductive polymer surface-treated with a conductive material, or a conductive polymer may be used.
[0074] The composition for forming a negative electrode active material layer prepared in the step (a) is applied onto a negative electrode current collector, and the current collector can be coated with an appropriate thickness depending on the thickness to be formed, which can be appropriately selected preferably within the range of 10 to 300 μm.
[0075] At this time, the method of applying the slurry-like composition for forming a negative electrode active material layer is not limited, and the negative electrode active material layer may be prepared by, for example, a doctor blade coating, a dip coating, a gravure coating, a slit die coating, a spin coating, a comma coating, a bar coating, a reverse roll coating, a screen coating, a cap coating, or the like.
[0076] After coating, the coating is dried, and finally, a negative electrode for a secondary battery (particularly a lithium secondary battery) having a negative electrode active material layer formed thereon can be produced.
[0077] A battery according to still another aspect of the present application may include a current collector and a negative electrode in which the negative electrode active material layer is formed on the current collector.
[0078] The battery may be a secondary battery (particularly, a lithium secondary battery) including a positive electrode, the negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.
[0079] The secondary battery may have a capacity retention rate of 80% or more when charged and discharged 200 times.
[0080] The secondary battery may have an electrode expansion rate of 60% or less when charged and discharged 200 times.
[0081] The configurations of the positive electrode, separator and electrolyte of the lithium secondary battery are not particularly limited in the present invention and may be any known configuration in this field.
[0082] The positive electrode includes a positive electrode active material formed on a positive electrode current collector.
[0083] The positive electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or those obtained by surface treatment with carbon, nickel, titanium, silver, etc. on the surface of aluminum or stainless steel can be used. At this time, the positive electrode current collector can be used in various forms such as a film, sheet, foil, net, porous body, foam, non-woven fabric body, etc. with fine irregularities formed on the surface so as to enhance the adhesive force with the positive electrode active material.
[0084] As the positive electrode active material constituting the positive electrode active material layer, all positive electrode active materials used in the technical field can be used. Specific examples of such positive electrode active materials include lithium metal; lithium cobalt-based oxides such as LiCoO2; Li 1+x Mn 2-x O4 (where x is 0 to 0.33), lithium manganese-based oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxides such as Li2CuO2; vanadium oxides such as LiV3O8, LiFe3O4, V2O5, Cu2V2O7; LiNi 1-x M x O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga and x = 0.01 to 0.3) represented by lithium nickel-based oxides; LiMn 2-x M x O2 (where M = Co, Ni, Fe, Cr, Zn or Ta and x = 0.01 to 0.1) or lithium manganese composite oxides represented by Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); Li(Ni a Co b Mn c )O2 (where 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1) represented by lithium-nickel-manganese-cobalt-based oxides; sulfur or disulfide compounds; phosphates such as LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4; Fe2(MoO4)3, etc. can be mentioned, but it is not limited to only these.
[0085] In this case, the positive electrode active material layer may further include a binder, a conductive material, a filler, and other additives in addition to the positive electrode active material, and the conductive material is the same as that described above in the negative electrode for the lithium secondary battery.
[0086] Examples of the binder include, but are not limited to, polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polymethacrylic acid (PMA), polymethyl methacrylate (PMMA), polyacrylamide (PAM), polymethacrylamide, polyacrylonitrile (PAN), polymethacrylonitrile, polyimide (PI), chitosan, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof.
[0087] The separator may be made of a porous substrate. The porous substrate may be any porous substrate typically used in electrochemical devices, such as, but not limited to, a polyolefin-based porous membrane or nonwoven fabric.
[0088] The separation membrane may be a porous substrate made of any one selected from the group consisting of polyethylene, polypropylene, polybutylene, polypentene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalate, or a mixture of two or more of these.
[0089] The electrolyte of the lithium secondary battery is a non-aqueous electrolyte containing a lithium salt, and is composed of a lithium salt and a solvent. As the solvent, a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, or the like is used.
[0090] The lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte solution, and examples of the lithium salt include LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB 10 Cl 10 , LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiC4BO8, LiCF3CO2, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiN(SO2F)2, LiN(SO2C2F5)2, LiC4F9SO3, LiC(CF3SO2)3, (CF3SO2)·2NLi, lithium chloroborane, lithium lower aliphatic carboxylates, and lithium 4-phenylborate imide can be used.
[0091] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydroxyfuran (franc), 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, 4-methyl-1,3-dioxene, diethyl ether, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, and ethyl propionate.
[0092] Examples of the organic solid electrolyte that can be used include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing secondary dissociation groups.
[0093] Examples of the inorganic solid electrolyte that can be used include nitrides, halides, and sulfates of Li, such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2.
[0094] The non-aqueous electrolyte may further contain other additives for the purpose of improving charge / discharge characteristics, flame retardancy, etc. Examples of the additives include pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum trichloride, fluoroethylene carbonate (FEC), propene sultone (PRS), vinylene carbonate (VC), etc.
[0095] The lithium secondary battery according to the present invention can be manufactured by lamination stacking of separators and electrodes and folding processes in addition to the general winding process, and the battery case may be cylindrical, square, pouch-shaped, or coin-shaped. EXAMPLES
[0096] The present application will be described in more detail below using examples, but the present application is not limited thereto.
[0097] [Production Example 1] Production of the first copolymer Vinyl acetate and N-vinyl formamide were continuously fed into a nitrogen-purged reactor and reacted at 60°C to synthesize a copolymer of vinyl acetate and vinyl formamide (PVAc-co-PVNF).
[0098] The mixture containing the synthesized PVAc-co-PVNF was collected and poured into methanol in which KOH was dissolved to hydrolyze the acetate functional groups of PVAc-co-PVNF, thereby obtaining a copolymer of vinyl alcohol and N-vinylformamide (PVOH-co-PVNF) in the form of a swollen gel.
[0099] The resulting gel was pulverized into fine particles, washed with methanol, and then added to methanol containing an alkaline catalyst for further hydrolysis. The soluble salts and by-products were removed by washing to obtain a first copolymer of vinyl alcohol and vinylamine (PVOH-co-PVAm).
[0100] [Production Example 2] Production of the second copolymer 1,050 g of distilled water and 10 g of alkyldiphenyloxide disulfonate were placed in a reactor, and the mixture was stirred for 1 hour while blowing in nitrogen.
[0101] Then, 2.5g of potassium persulfate was added and the temperature of the reactor was raised to 60°C. Then, 110g of vinyl acetate and 330g of ethyl acrylate were added dropwise for 3 hours, and the reaction was terminated by maintaining the temperature for 2 hours to obtain a vinyl acetate-ethyl acrylate copolymer with a solid content of 30% by weight.
[0102] A reactor was charged with 100 g of vinyl acetate-ethyl acrylate copolymer having a solid content of 30%, 150 g of ethanol, hydroxide and organic salt, and hydrolysis was allowed to proceed with stirring at 60° C. for 4 hours.
[0103] After completion of the hydrolysis, the precipitated hydrolyzate was dissolved in distilled water, heated to 80° C., and stirred and stripped for 8 hours to produce a second copolymer.
[0104] [Production Example 3] Production of lithium secondary battery A negative electrode slurry was prepared by mixing 88 g of artificial graphite as an electrode active material, 8 g of SiOx, 1 g of carbon nanotubes, 3 g of a binder including the first copolymer prepared in Preparation Example 1 and / or the second copolymer prepared in Preparation Example 2, and distilled water.
[0105] The prepared negative electrode slurry was uniformly coated on a copper current collector, dried at 110° C., and the resulting mixture was rolled and heated in a vacuum oven at 110° C. for 4 hours or more to prepare a negative electrode.
[0106] Thereafter, a non-aqueous electrolyte solution containing a lithium salt was used as an electrolyte, and a polyolefin separator was interposed between the positive electrode and the negative electrode, and a lithium secondary battery was manufactured without being classified into a pouch or coin cell type.
[0107] The non-aqueous electrolyte used was a solution of LiPF6 electrolyte at a concentration of 1M in a solvent in which ethylene carbonate: ethyl methyl carbonate: diethyl carbonate were mixed in a volume ratio of 3:5:2.
[0108] [Example 1] A lithium secondary battery was manufactured according to Manufacturing Example 3 using a binder in which the first copolymer manufactured according to Manufacturing Example 1 and the second copolymer manufactured according to Manufacturing Example 2 were mixed in a weight ratio of 50:50 (weight % of the first copolymer:weight % of the second copolymer).
[0109] [Example 2] A lithium secondary battery was produced in the same manner as in Example 1, except that the weight ratio of the first copolymer to the second copolymer (weight % of the first copolymer:weight % of the second copolymer) was set to 30:70.
[0110] [Example 3] A lithium secondary battery was produced in the same manner as in Example 1, except that the weight ratio of the first copolymer to the second copolymer (weight % of the first copolymer:weight % of the second copolymer) was 20:80.
[0111] [Example 4] A lithium secondary battery was produced in the same manner as in Example 1, except that the weight ratio of the first copolymer to the second copolymer (weight % of the first copolymer:weight % of the second copolymer) was 70:30.
[0112] [Example 5] A lithium secondary battery was produced in the same manner as in Example 1, except that the weight ratio of the first copolymer to the second copolymer (weight % of the first copolymer:weight % of the second copolymer) was 80:20.
[0113] [Comparative Example 1] A lithium secondary battery was produced in the same manner as in Example 1, except that a binder containing only the first copolymer (a binder without the second copolymer) was used.
[0114] [Comparative Example 2] A lithium secondary battery was produced in the same manner as in Example 1, except that a binder containing only the second copolymer (a binder containing no first copolymer) was used.
[0115] [Comparative Example 3] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the weight ratio of styrene-butadiene rubber (SBR) to carboxymethyl cellulose (CMC) (weight % of SBR:weight % of CMC) was 45:55.
[0116] [Evaluation Example 1] Evaluation of the stability of negative electrode slurry The stability of the negative electrode slurries of Examples 1 to 5 and Comparative Example 1 was measured at room temperature using a grind gauge.
[0117] As a result of the measurement, the particle size of the negative electrode slurry in Examples 1 to 5, in which the binder in which the first copolymer and the second copolymer were mixed at a certain ratio was used, was 25 μm or more, whereas the particle size of the negative electrode slurry in Comparative Example 1, in which the binder consisting of the first copolymer alone was used, was measured to be 35 μm or more.
[0118] That is, it was confirmed that the particle size of the negative electrode slurries of Examples 1 to 5 was lower than the particle size of the negative electrode slurry of Comparative Example 1, and the dispersibility and stability of the negative electrode slurries of Examples 1 to 5 were improved compared to the dispersibility and stability of the negative electrode slurry of Comparative Example 1.
[0119] On the other hand, the particle size of the negative electrode slurry of Comparative Example 2, in which only the second copolymer was used as a binder, was measured to be 20 μm or more.
[0120] [Evaluation Example 2] Evaluation of binder binding strength In order to measure the binding strength of the binders used in Examples 1 to 5 and Comparative Examples 1 to 3, the copper current collector of the manufactured negative electrode and the negative electrode slurry layer formed on the copper current collector were peeled off by 180°, and the binding strength was measured.
[0121] [Evaluation Example 3] Battery performance evaluation The lithium secondary batteries produced in Examples 1 to 5 and Comparative Examples 1 to 3 were charged and discharged twice at 25° C., with a charge / discharge current density of 0.1C, a charge cut-off voltage of 4.8V, and a discharge cut-off voltage of 2.7V.
[0122] Thereafter, the battery was charged and discharged 200 times with a charge / discharge current density of 1C, a charge cut-off voltage of 4.8V, and a discharge cut-off voltage of 2.7V, to measure the capacity retention rate.
[0123] All discharges were performed under constant current / constant voltage conditions, and the constant voltage discharge cut-off current was set to 0.005C.
[0124] At this time, the capacity retention rate was calculated according to the following formula 1.
[0125] (Formula 1) Capacity retention rate (%) = (discharge capacity after 200 cycles / discharge capacity after 3 cycles) x 100
[0126] After the charge / discharge evaluation was completed, the cell was disassembled to check the change in thickness of the negative electrode, and the silicon expansion suppression effect of the binders used in Examples 1 to 5 and Comparative Examples 1 to 3 was compared.
[0127] At this time, the thickness change rate was calculated by the following Equation 2.
[0128] (Formula 2) Electrode expansion rate (%) = (thickness of negative electrode after 200 cycles - thickness of negative electrode vacuum-dried before assembly) / thickness of negative electrode vacuum-dried before assembly × 100
[0129] The binding strength of the binder, the battery capacity retention rate, and the electrode expansion rate measured in Evaluation Examples 2 and 3 are shown in Table 1 below.
[0130] [Table 1]
[0131] As shown in Table 1, in Examples 1 to 5, in which a binder in which the first copolymer and the second copolymer were mixed at a certain ratio was used, it was confirmed that the binding strength was superior to that of Comparative Example 2, in which a binder consisting of only the second copolymer was used.
[0132] In addition, it was found that when the first copolymer and the second copolymer were mixed and used as a binder, the higher the mixing ratio of the first copolymer, the more improved the binding strength.
[0133] On the other hand, in the case of Examples 1 to 5 in which a binder in which the first copolymer and the second copolymer were mixed at a certain ratio was used, it was confirmed that the capacity retention rate of the lithium secondary battery after 200 cycles was 80% or more.
[0134] In contrast, in Comparative Example 1 or 2 in which the first copolymer or the second copolymer alone was used as the binder, the capacity retention rate of the lithium secondary battery decreased.
[0135] In terms of the electrode expansion rate after 200 cycles of the lithium secondary battery, it was confirmed that in Examples 1 to 5, in which a binder in which the first copolymer and the second copolymer were mixed at a certain ratio was used, the electrode expansion rate was suppressed to 55% or less.
[0136] In contrast, Comparative Example 1, in which the first copolymer alone was used as the binder, and Comparative Example 3, in which a binder was used by mixing the first copolymer with a conventional binder polymer, showed a relatively high electrode expansion coefficient.
[0137] A high electrode expansion rate can shorten the lifespan of a lithium secondary battery and can lead to serious failures, such as fire.
[0138] That is, when a binder consisting of only the first copolymer is used, the binding strength may be higher than that of a binder in which the first copolymer and the second copolymer are mixed at a certain ratio, but the capacity retention rate of the lithium secondary battery may decrease and the electrode expansion rate may increase, resulting in a decrease in battery characteristics.
[0139] In addition, when the binder is made of only the second copolymer, the electrode expansion rate can be suppressed more effectively than when the binder is made of a mixture of the first copolymer and the second copolymer in a certain ratio. However, the binding strength and the capacity retention rate of the lithium secondary battery may decrease, resulting in a decrease in the battery characteristics.
[0140] As a result, it was confirmed that the copolymer binder composition of the present application, in which the first copolymer and the second copolymer are mixed in a certain ratio, has an appropriate range of dispersion stability of the negative electrode slurry composition, binding strength of the negative electrode, and secondary battery characteristics.
[0141] On the other hand, when the first copolymer or the second copolymer is used alone or mixed with an existing polymer to be used as a binder, it was found that one or more of the dispersion stability of the negative electrode slurry composition, the binding strength of the negative electrode, and the properties of the secondary battery are not suitable for use in an actual secondary battery.
[0142] The scope of the present invention is indicated by the claims set forth below rather than by the above detailed description, and all modifications and variations that fall within the meaning and scope of the claims and their equivalent concepts should be interpreted as being included in the scope of the present invention. [Industrial Applicability]
[0143] The copolymer composition of the present invention has excellent flexibility, water solubility and dispersibility, and improves the dispersion stability of the negative electrode slurry composition. It also enhances the binding strength with the negative electrode current collector, suppresses the expansion of the negative electrode, and improves the capacity retention rate per cycle of the secondary battery.
Claims
1. A first copolymer including a vinyl alcohol monomer unit and a vinyl amine monomer unit; a second copolymer including a vinyl alcohol monomer unit and an acrylic acid salt-based monomer unit; Copolymer composition.
2. The first copolymer additionally includes at least one selected from the group consisting of vinyl acetate monomer units and N-vinylformamide monomer units; The second copolymer further includes at least one selected from an acrylate monomer unit and a vinyl acetate monomer unit. The copolymer composition of claim 1.
3. The vinylamine monomer unit is at least one selected from the group consisting of vinylamine and 1-methylvinylamine; The acrylic acid salt monomer unit is at least one selected from the group consisting of acrylic acid and methacrylic acid; The copolymer composition of claim 1.
4. The N-vinylformamide monomer unit is at least one selected from the group consisting of N-vinylformamide and N-isopropenylformamide; The acrylate-based monomer unit is at least one selected from the group consisting of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, sec-butyl acrylate, sec-butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, and ethylhexyl methacrylate. The copolymer composition of claim 2.
5. The first copolymer contains 50 mol % or more and 90 mol % or less of the vinyl alcohol monomer unit and 1 mol % or more and 50 mol % or less of the vinylamine-based monomer unit, based on a total content of 100 mol % of the first copolymer. The copolymer composition of claim 1.
6. The second copolymer contains 1 mol % to 30 mol % of the vinyl alcohol monomer unit and 50 mol % to 90 mol % of the acrylic acid salt-based monomer unit, based on a total content of 100 mol % of the second copolymer. The copolymer composition of claim 1.
7. The first copolymer is represented by the following formula 1: The second copolymer is represented by the following formula 2: The copolymer composition of claim 1. 【Chemistry 1】 In the above Chemical Formula 1, 0≦x≦15 mol%, 50≦y≦90 mol%, 0≦m≦30 mol%, and 1≦n≦50 mol%. 【Chemistry 2】 In the above Chemical Formula 2, R 1 and R 2 are different or the same and each independently represents hydrogen or a linear or branched hydrocarbon having 1 to 5 carbon atoms; R 3 is a hydroxide (—OH) group, M is an alkali metal; 0≦a≦5 mol%, 50≦b≦90 mol%, 0≦c≦5 mol%, and 1≦d≦30 mol%.
8. The copolymer composition contains 10% by weight or more and 90% by weight or less of the first copolymer and 10% by weight or more and 90% by weight or less of the second copolymer, based on a total weight of 100% by weight of the copolymer composition. The copolymer composition of claim 1.
9. the first copolymer is a random or block copolymer; The second copolymer is a random or block copolymer; The copolymer composition of claim 1.
10. The number average molecular weight of the first copolymer is 10,000 or more and 1,000,000 or less, The number average molecular weight of the second copolymer is 10,000 or more and 1,000,000 or less. The copolymer composition of claim 1.
11. The copolymer composition according to any one of claims 1 to 10, A negative electrode active material, Anode slurry.
12. A current collector; a negative electrode active material layer formed on the current collector, the negative electrode active material layer comprising the copolymer composition according to any one of claims 1 to 10; Negative electrode.
13. The negative electrode according to claim 12, Secondary battery.
Citation Information
Patent Citations
Negative electrode for lithium secondary battery, and lithium secondary battery containing this
JP2009135103A
Binder composition for lithium secondary battery, and lithium secondary battery electrode and lithium secondary battery including the same
JP2012064574A
Active material for nonaqueous secondary battery negative electrodes, negative electrode arranged by use thereof, and nonaqueous secondary battery
JP2015187985A
Nonaqueous electrolyte secondary battery negative electrode, binder for nonaqueous electrolyte secondary battery negative electrode, and nonaqueous electrolyte secondary battery
WO2017188032A1
Binder composition for non-aqueous electrolyte batteries, and binder aqueous solution for non-aqueous electrolyte batteries, slurry composition for non-aqueous electrolyte batteries, electrode for non-aqueous electrolyte batteries and non-aqueous electrolyte battery each utilizing same
WO2018225539A1
Cited By
Binder containing copolymer composition, negative electrode for secondary battery containing said binder, and secondary battery containing said negative electrode
JP2025534715A
A binder comprising a copolymer composition, a negative electrode for a secondary battery comprising the binder, and a secondary battery comprising the negative electrode.
JP7926653B2